Benign design intumescent flame-retarding aliphatic waterborne polyester coatings modified by precipitated silica aerogel and aluminum powder - YaChao Wang (Elsevier, 2021)
The organic-inorganic hybrid intumescent flame retardant coatings (IFRCs) is an efficient and ecological strategy to obtain excellent fireproof performance. The benign design on aliphatic waterborne polyester (AWP)-based IFRCs is modified by silicon-based aerogels and aluminum powder simultaneously, which is characterized by various techniques to explore the flame retardant mechanism. The results show that an appropriate precipitated silica aerogel (0.45 wt%) and aluminum powder (0.8 wt%) impart synergetic flame-retarding and smoke suppression effect to the AWP-based IFRCs, evidenced by the reduced fire growth index of 0.50 from 0.63 kW m−2 s−1, as well as the raised flame retardancy index of 2.52 from 1. Because the labyrinth barrier effect of amorphous silica-alumina gels derives from the in-situ cross-linking between the active Si(OH)4 and AlOOH or Al(OH)3, as well as the enhanced adhesive property between silanols and plywood surface, which facilitates the ceramic-like charring of AWP-based IFRCs, leading to the formation of continuous and tortuous char. It expands the design methods and flame-retarding mechanism of ecological organic-inorganic hybrid IFRCs.